When Tenants Claimed the City : The Struggle for Citizenship in New York City Housing - Gold, Roberta (Book collections on Project MUSE., 2014)
In postwar America, not everyone wanted to move out of the city and into the suburbs. For decades before World War II, New York's tenants had organized to secure renters' rights. After the war, tenant activists raised the stakes by challenging the newly-dominant ideal of homeownership in racially segregated suburbs. They insisted that renters as well as owners had rights to stable, well-maintained homes, and they proposed that racially diverse urban communities held a right to remain in place. Further, the activists asserted that women could participate fully in the political arenas where these matters were decided. This work shows that New York City's tenant movement made a significant claim to citizenship rights that came to accrue, both ideologically and legally, to homeownership in postwar America.